Talampicillin: a new derivative of ampicillin. Issue 6022 (5th June 1976) - Leigh, D A; Reeves, D S; Simmons, K; Thomas, A L; Wilkinson, P J
Abstract : Talampicillin is a thiazolide carboxylic ester of ampicillin and is hydrolysed in the intestinal mucosa to release free ampicillin. The mean peak serum concentration of ampicillin occurred one hour after a dose of talampicillin and was about twice that attained by an equivalent dose of ampicillin. The presence of food in the stomach reduced and delayed the peak blood levels but did not affect the total amount of antibiotic absorbed or the urinary recovery. Talampicillin had less effect on the faecal flora in volunteers than ampicillin, and no overgrowth with Candida spp or Staphylococcus aureus was seen. Thirty-eight out of 47 urinary infections were eradicated by a seven-day course of talampicillin.